A stable strain gauge measurement method for monitoring in-situ stress. Issue 4 (October 2021) - Jiang, Jingjie; Sun, Yao; Peng, Hua; Ma, Xiumin
Abstract: In-situ stress exists in all rock mass or structures, which is reflected in the deformation and failure of various underground or ground excavation in geotechnical engineering. In-situ widely used in the engineering practice, in-situ stress monitoring plays an important role in many aspects, such as mine development, slope support, and geological disaster prevention and control, etc. Strain gauge has been used to record rock deformation using Differential strain analysis (DSA), Hollow Inclusion Technique (CSIRO Cells), and other in-situ stress measurement techniques. Limited by the volume, cost, power, and connection scheme of the measuring instruments, the test data are always influenced by various immeasurable factors, such as bend of the measuring cable and change in the ambient temperature. Majority of the gauge measurement technologies are not suitable for in-situ stress monitoring because of the stability of strain gauge measurement is poor, limits the application range of the gauge measurement. A stable strain gauge measurement method can be used for medium to high-precision in-situ stress monitoring to serve various engineering developments. We made a new measurement scheme by using high-precision constant current with independent signal transmission channels to achieve a high stability and high-resolution strain gauge measurement circuit with low power consumption and space cost. The temperature drift is as low as 0.3 με/°C in 0°C–60°C temperature range at 8000 με strain input, which can achieve the measurement effect of the traditional desktop strain gauge in about 1/10th volume and very low cost. The error caused by the change of cable resistance is reduced to 1 ppm, and the error caused by the disconnection and reconnection is less than 1 με, which avoids the failures caused by various environmental factors in the monitoring process, and the installation distance of monitoring strain gauge can reach tens of meters. This creates conducive conditions for using traditional in-situ stress measurement technology with in-situ stress monitoring and establishes an efficient and low-cost in-situ stress monitoring system.